Efficient and selective oxidation of sulfur mustard using singlet oxygen generated by a pyrene-based metal–organic framework. Issue 36 (23rd August 2016) - Liu, Yangyang; Buru, Cassandra T.; Howarth, Ashlee J.; Mahle, John J.; Buchanan, James H.; DeCoste, Jared B.; Hupp, Joseph T.; Farha, Omar K.
Abstract : Singlet oxygen generated by a metal–organic framework under UV LED irradiation selectively oxidizes sulfur mustard to nontoxic products. Abstract : A pyrene-based metal–organic framework (MOF) NU-1000 was used as a heterogeneous photocatalyst for the degradation of a sulfur mustard simulant, 2-chloroethyl ethyl sulfide (CEES). Using irradiation from a commercially available and inexpensive ultraviolet (UV) light-emitting diode (LED), singlet oxygen ( 1 O2 ) is generated by NU-1000 and selectively oxidizes CEES to the nontoxic product 2-chloroethyl ethyl sulfoxide (CEESO). More importantly, this method was tested on the warfare agent sulfur mustard (HD) for the first time using 1 O2 and a MOF catalyst, and this method proved to be effective in oxidizing sulfur mustard to nontoxic products without forming the toxic sulfone by-product.